Нові результати щодо утворення ϕ (1020) в експерименті NA61/SHINE у CERN SPS - for the NA61/SHINE Collaboration, A. Marcinek (Publishing house "Academperiodika", 2026)
NA61/SHINE is a multipurpose, fixed-target hadron spectrometer at the CERN SPS. Its research program includes studies of strong interactions as well as reference measurements for neutrino and cosmic-ray physics. A significant advantage of NA61/SHINE over collider experiments is its extended coverage of phase space available for particle production. This includes the entire projectile hemisphere of the collision, with no low-pT cut-off. The energy and systemsize dependence of strangeness production play an essential role in studies of the transition from confined to deconfined matter. With its zero net strangeness and its valence structure composed predominantly of s and -s valence quarks, the φ(1020) meson will not be sensitive to strangeness-related effects in a purely hadronic scenario, but will behave like a doubly strange particle in a partonic system. This paper presents the first-ever results on φ(1020) meson production in intermediate-size systems at the CERN SPS, that is, central Ar + Sc collisions at √SNN = 8.8, 11.9, and 16.8 GeV. The presented results include double-differential rapiditytransverse momentum (y-pT) distributions, transverse mass (mT) spectra at midrapidity, pT integrated rapidity spectra, mean multiplicities (4π yields), and particle ratios. These are compared to data on Pb + Pb and p + p collisions. A discussion of open and hidden strangeness production enhancement is included. Finally, a comparison with three microscopic models is shown, demonstrating their overall failure to describe these new measurements.